A study of 22 Cases of Dorsal Inter-Vertebral Disc Prolapse treated by Thoracic Laminectomy - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: dorsal spine intervertebral disc prolapse (IVDP) not a very common entity compared with cervical & lumbar region usually treated surgically.Patients & method: 22 patients studied in the specialized surgical hospital neurosurgical department from Jan 2002 till Jan. 2006. the study included age, gender, cases. clinical features, diagnoses & surgical management.Results: 22 patients were studied 76% of the patients are at the age of 30-60 with slight male predominance, all diagnosed by MRI & or CT scan, all managed surgically by laminectomy the results are compared with other studies.Conclusion: posterior thoracic laminectomy at the dorsal region is a safe, simple procedure with good results if done early & meticolous.